On social and philosophical problems of technology. Review of the monograph-essay by N.M. Tverdynin "Man in the technoworld: book and reality" - Yakovleva, Lyubov E. (Semiotic studies, 2024)
The introductory part of the review provides a description of a new genre of research into the problems of the philosophy of technology. The main part of the review is devoted to examining the structure of the work, which includes an analysis of technical devices emerging in the history of human society and an assessment of their application through the prism of literature; excerpts from the story "After the Feat" about the liquidators of the Chernobyl accident; a study of the dilemma of technocracy and technophobia. It is important to consider three levels of technical creativity: rationalization, invention, scientific and technical creativity. Measures of social support for the revival of inventive and scientific and technical activities are proposed.